Pot-Pollen Volatiles, Bioactivity, Synergism with Antibiotics, and Bibliometrics Overview, Including Direct Injection in Food Flavor - Patricia Vit; Maria Araque; Bajaree Chuttong; Enrique Moreno; Ricardo R. Contreras; Qibi Wang; Zhengwei Wang; Emanuela Betta; Vassya Bankova (Foods)
Stingless bees (Hymenoptera; Apidae; Meliponini), with a biodiversity of 605 species, harvest and transport corbicula pollen to the nest, like Apis mellifera, but process and store the pollen in cerumen pots instead of beeswax combs. Therefore, the meliponine pollen processed in the nest was named pot-pollen instead of bee bread. Pot-pollen has nutraceutical properties for bees and humans; it is a natural medicinal food supplement with applications in health, food science, and technology, and pharmaceutical developments are promising. Demonstrated synergism between Tetragonisca angustula pot-pollen ethanolic extracts, and antibiotics against extensively drug-resistant (XDR) bacteria revealed potential to combat antimicrobial resistance (AMR). Reviewed pot-pollen VOC richness was compared between Australian Austroplebeia australis (27), Tetragonula carbonaria (31), and Tetragonula hogkingsi (28), as well as the Venezuelan Tetragonisca angustula (95). Bioactivity and olfactory attributes of the most abundant VOCs were revisited. Bibliometric analyses with the Scopus database were planned for two unrelated topics in the literature for potential scientific advances. The top ten most prolific authors, institutions, countries, funding sponsors, and sources engaged to disseminate original research and reviews on pot-pollen (2014–2023) and direct injection food flavor (1976–2023) were ranked. Selected metrics and plots were visualized using the Bibliometrix-R package. A scholarly approach gained scientific insight into the interaction between an ancient fermented medicinal pot-pollen and a powerful bioanalytical technique for fermented products, which should attract interest from research teams for joint projects on direct injection in pot-pollen flavor, and proposals on stingless bee nest materials. Novel anti-antimicrobial-resistant agents and synergism with conventional antibiotics can fill the gap in the emerging potential to overcome antimicrobial resistance.